The effects of celebrity endorsement on the consumers’ perceptions towards global brands - Popa, Victor (2016)
Brands are those lifestyles which consumers chose to buy in order to gain the value offered by the company, in order to be part of the community created through the brand equity elements and validated in the purchase of the products. Companies have understood how important it is to build a strong brand and many of them spend millions on aligning the brand with the design and style of the products, projecting the face and values of the company into the advertising campaigns. One of the most popular methods is through endorsement, placing a renounced celebrity and leveraging on the positive feedback of those customers that also follow the activities of the star whose face is on the cover of the marcom campaign. Celebrities have been used for a very long time to promote brands, sell products and services. Research has shown that those spokesmen of a brand who are more attractive can improve the statistics of recall and appeal more interest to the promotion campaign, as well as influence more on customer’s intention of buying the product (Kahle and Homer, 1985). The main purpose of this research is to investigate how celebrity endorsements influence the brand equity dimensions (brand loyalty, brand awareness, perceived quality and brand associations) as well as stimulate consumers’ word-of-mouth through brand identification, growth in interest and the advertising memorability. The hypotheses were tested with the aid of Structural Equation Modelling (SEM) in the PLS (Partial Least Squares) software. The survey is comprised of a target group of 589 respondents, from three countries – Brazil, Moldova and Portugal. Results evidence that the Attitude towards the Celebrity influences different Brand Equity dimensions and affects brand identification, growth in advertisement interest and advertising memorability, generating positive word of mouth (or negative, depending on the type of advertisement and reputation). Based on these findings we suggest further investigation in this area with the possibility to gain more data about the different fields of marcom and the different types of CE which are more appropriate for the given type of business.